Dermatomyositis Associated with Celiac Disease: Response to a Gluten-Free Diet. (2006) - Song, Min Soo; Farber, David; Bitton, Alain; Jass, Jeremy; Singer, Michael; Karpati, George
Abstract : The association between dermatomyositis and celiac disease in children has been well documented. In the adult population, however, the association has not been clearly established. A rare case of concomitant dermatomyositis and celiac disease in a 40-year-old woman is presented. After having been diagnosed with dermatomyositis and iron deficiency anemia, this patient was referred to the gastroenterology clinic to exclude a gastrointestinal malignancy. Blood tests revealed various vitamin deficiencies consistent with malabsorption. The results of gastroscopy with duodenal biopsy were consistent with celiac disease. After she was put on a strict gluten-free diet, both nutritional deficiencies and the dermatomyositis resolved. The patient's human leukocyte antigen haplotype study was positive for DR3 and DQ2, which have been shown to be associated with both juvenile dermatomyositis and celiac disease. It is suggested that patients with newly diagnosed dermatomyositis be investigated for concomitant celiac disease even in the absence of gastrointestinal symptoms.